PENGARUH LABEL HALAL DAN HARGA TERHADAP KEPUTUSAN PEMBELIAN PRODUK YAKULT DI KOTA BIMA - Putra, Anzalna; Ernawati, Sri (JURSIMA, 2023)
For Muslims, halal labeling is a material consideration in purchasing, as well as price. The purpose of this study was to determine the effect of halal labels and prices on purchasing decisions both partially and simultaneously. This type of research is associative, the research instrument uses a questionnaire with a Likert scale. The population used in this study were all consumers of yakul products in the city of Bima whose number is unknown (unknown population). The number of samples used in this study were 50 respondents using a purposive sampling technique. Data collection techniques with observation, questionnaires, and literature study. Data analysis techniques by carrying out validity tests, reliability tests, multiple linear regression tests, correlation coefficients, determination tests, t tests, and f tests. The results of this study indicate that the halal label has no significant effect while the price has a significant effect on the purchasing decision, while simultaneously the halal label and price have an effect on the purchasing decision.